Disruptive technology and public security: an analysis of the worldwide scientific production (Research, Society and Development, 2022)
The objective of this research is to identify which disruptive technologies, focusing on artificial intelligence, are being adopted and researched worldwide. The research conducted in an integrative manner in journal databases (IEEE Xplore, Science Direct, Web of Science, Scopus and Dimensions) and other search engines such as Google Scholar, to complement the data concerning researchers and publications, is presented. The research identifies the preference for publications in repositories of preprints, the countries, authors, institutions and publishers with the largest number of publications. After conducting content analysis on the main documents, the technologies and main applications of disruptive technologies are identified, with a focus on artificial intelligence in public security. In the analyses conducted, the technologies that stand out are the internet of things, big data, and blockchain. The results indicate which disruptive technologies, with a focus on artificial intelligence, are being adopted and researched worldwide, and for what purpose. Additionally, it highlights legislation as the main concern found in the papers and research opportunities and trends.